Antifouling surface for biomedical devices: Modification of COC surface by quaternary ammonium moieties via diazonium chemistry - Nikiforova K. A. Ksenia Alekseevna; Gorbunova A. Alina; Plotnikov E. V. Evgeny Vladimirovich; Postnikov P. S. Pavel Sergeevich; Guselnikova O. A. Olga Andreevna (2022, 2022)
Title screen